Morphological variation of coronoid process, sigmoid notch, and condylar process among patients of tertiary care centre of Nepal - Chaulagain, Rajib; Chaudhary, Sanjeeb; Poudel, Prashamsa; Gautam, Ajeevan (Journal of Kathmandu Medical College, 2022)
Background: Mandibular ramus undergoes remodelling with time. The remodeling is also influenced by factors such as ageing, dental status, gender, stress, trauma, force exerted during occlusion, and joint diseases. Studies have reported variations in morphology of coronoid process, condylar process, and sigmoid notch of the mandible. Objectives: To assess the morphological variations of processes of mandible and the sigmoid notch in a tertiary care centre of Nepal. Methods: A retrospective study was conducted at Chitwan Medical College. This study included 310 orthopantomograms (OPGs) retrieved from the archives of the hospital data from 2022 May-June. All OPGs were taken with same radiographic equipment. Data taken in predesigned proforma were entered and analysed in SPSS v.16. Descriptive statistics was used to explain the results in tabulated form. Results: Among 310 OPGs assessed, 188 (60.6%) were female and rest male. Angled mandibular condyle was prevalent on both right 123 (39.7%) and left side 134 (43.2%). More than 50% of sigmoid notch was of sloping shape on both right and left side. Triangular type of coronoid process was present 185 (59.7%) on right side and 183 (59.0%) on left side. Among the coronoid process types, triangular was found more in male and females on both right and left sides. Conclusion: This study concluded that the angled type of condylar process, sloping type of sigmoid notch, and triangular type of coronoid process were more prevalent on both right and left side. All three parameters were also observed to be prevalent in females suggesting gender variation.